Black Hole Ejected from the Nucleus of Galaxy NGC 5236 - Dottori, H. (2010)
The Fanaroff-Riley II-type radiosource J 133658.3-295105, which is also an X-ray source, appears to be projected onto the disc of the barred-spiral galaxy NGC 5236 (M 83) at about 1.2 kiloparsecs from the galaxy´s optical nucleus. J 133658.3-295105, its radio-lobes, and two other radiosources, neither of which are supernovae remnants or HII regions, are aligned with the optical nucleus of NGC 5236. Due to this peculiar on-the-sky projection, we studied J 133658.3-295105 using GEMINI+GMOS optical spectroscopy and also reanalyzed Chandra spectroscopy which was carried out in 2000. We marginally detected the Hα emission line receding at 130 km/sec with respect to the optical nucleus. We also demostrate that J 133658.3-295105 presents the Fe-Kα emission line at a redshift z = 0.018 ± 0.01. Both, Hα and Fe-Kα present redshifts that are compatible with the distance of NGC 5236. That findings reinforce the scenario of a local object for J 133658.3-295105, which could have been ejected from the nucleus of NGC 5236.